Orexins and fear: implications for the treatment of anxiety disorders. Issue 9 (September 2015) - Flores, África; Saravia, Rocío; Maldonado, Rafael; Berrendero, Fernando
Highlights: We review the role of orexins in the modulation of the neural circuits of fear. We describe the effects of orexin antagonists in animal models of anxiety disorders. We discuss the implications of this research for the treatment of anxiety disorders. Abstract : An understanding of the neurobiological mechanisms involved in the regulation of fear is essential for the development of new treatments for anxiety disorders, such as phobias, panic, and post-traumatic stress disorders (PTSD). Orexins, also known as hypocretins, are neuropeptides located exclusively in hypothalamic neurons that have extensive projections throughout the central nervous system. Although this system was initially believed to be primarily involved in the regulation of feeding behavior, recent studies have shown that orexins also modulate neural circuits implicated in the expression and extinction of fear memories. Here, we discuss recent findings involving orexins in anxiety disorders and current clinical trials using orexin ligands that could be applied to identify new therapies for diseases characterized by pathological fear.